Pengaruh Metode Mengajar Guru dan Kemandirian Belajar Terhadap Prestasi Belajar Siswa Madrasah Aliyah Kab. Kudus - Rofiq Faudy Akbar (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
Student achievement can be regarded as indicators of the success of a learning process, which is a measure of success for teachers to conduct the necessary improvements. This study aimstodetermine the effect ofteaching methodthatis appliedandindependent learningon student achievement. The research method is quantitative by using multiple regression analysis. The respondents are students of class XII Madrasah Aliyah in Kudus, the number of sample is 187 students from 17 schools. The results of the study revealed that teachers’ teaching method and student learning independence affect learning achievement of 56.9%. Teacher’steaching style and student learning independence significant positive effect on learning achievement with a significance level less than 1%.